ANALISIS KEADILAN RESTORATIF DALAM TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA GOLONGAN I (PUTUSAN NOMOR 1129/PID.SUS/2021/PN.JKT.UTR): Analysis Of Restorative Justice In Criminal Act Of Narcotics Abuse Group I (Decision Number 1129/Pid.Sus/2021/Pn.Jkt.Utr) - Aprillia Tiara Yunita; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2024)
The process of resolving criminal cases involving narcotics abuse through rehabilitation is implemented based on the principles of restorative justice, taking into consideration judicial principles such as cost-effectiveness, simplicity, speed. Narcotics abuse is considered a criminal offense requiring specialized handling. This research centers around the application of Restorative Justice in Criminal Cases of Narcotics Abuse in Group I, in accordance with the Narcotics Law. This study adopts a normative research approach utilizing secondary data. The nature of the research is descriptive, with qualitative data analysis and conclusions drawn through deductive reasoning. The research findings reveal that, despite the mandate for rehabilitation stipulated in Law Number 35 of 2009 concerning Narcotics, the practical implementation often deviates from legal provisions. The conclusion is based on Decision Number 1129/Pid.Sus/2021/PN.Jkt.Utr, the Panel of Judges was expected to adjudicate the Defendant for Drug Abuse, thereby warranting their provision of medical treatment, care, and rehabilitation within designated medical and/or social rehabilitation facilities.